HAK WARGA NEGARA DALAM MEMPEROLEH PENDIDIKAN DASAR DI INDONESIA - Nadziroh Nadziroh; Chairiyah Chairiyah; Wachid Pratomo (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2018)
Abstract : The right to obtain the basic education is the right of every citizen as stipulated in the constitution and the fulfillment of such right is a great respect for human rights. Indonesia is legal state that has guaranteed and regulated the legal protection of the right to basic education for Indonesian citizens aged seven to fifteen years.Â  In conducting basic level education has been done since the existence of 4th amendment of UUD1945 Constitution which further followed up with the Law on National Education System No. 20 of 2003. In Aditian, Law No. 39 of 1999 on Human Rights also provide legal protection for Indonesian citizens to be able to obtain the education although not explicit and explicit set free education at the basic level. The process of implementing basic education its responsibilities between local government and society. Funding of education is share responsibility between central government, local government and society.